Insulinotropic Effects of Neprilysin and/or Angiotensin Receptor Inhibition in Mice - Esser, Nathalie; Schmidt, Christine; Barrow, Breanne M.; Cronic, Laura; Hackney, Daryl J.; Mongovin, Stephen M.; Hogan, Meghan F.; Templin, Andrew T.; Castillo, Joseph J.; Hull, Rebecca L.; Zraika, Sakeneh (Frontiers in Endocrinology, 2022)
Treatment of heart failure with the angiotensin receptor-neprilysin inhibitor sacubitril/valsartan improved glycemic control in individuals with type 2 diabetes. The relative contribution of neprilysin inhibition versus angiotensin II receptor antagonism to this glycemic benefit remains unknown. Thus, we sought to determine the relative effects of the neprilysin inhibitor sacubitril versus the angiotensin II receptor blocker valsartan on beta-cell function and glucose homeostasis in a mouse model of reduced first-phase insulin secretion, and whether any beneficial effects are additive/synergistic when combined in sacubitril/valsartan. High fat-fed C57BL/6J mice treated with low-dose streptozotocin (or vehicle) were followed for eight weeks on high fat diet alone or supplemented with sacubitril, valsartan or sacubitril/valsartan. Body weight and fed glucose levels were assessed weekly. At the end of the treatment period, insulin release in response to intravenous glucose, insulin sensitivity, and beta-cell mass were determined. Sacubitril and valsartan, but not sacubitril/valsartan, lowered fasting and fed glucose levels and increased insulin release in diabetic mice. None of the drugs altered insulin sensitivity or beta-cell mass, but all reduced body weight gain. Effects of the drugs on insulin release were reproduced in angiotensin II-treated islets from lean C57BL/6J mice, suggesting the insulin response to each of the drugs is due to a direct effect on islets and mechanisms therein. In summary, sacubitril and valsartan each exert beneficial insulinotropic, glycemic and weight-reducing effects in obese and/or diabetic mice when administered alone; however, when combined, mechanisms within the islet contribute to their inability to enhance insulin release.